(untitled) (Revista Contexto & Saúde, 2025)
This study aims to identify tools for the early detection of clinical deterioration and their usability in preventing cardiopulmonary arrest. It is an integrative literature review conducted in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), and Nursing Database (BDENF). A total of 242 articles were identified, of which 12 were selected for descriptive synthesis. Most publications occurred between 2015 and 2022, with a peak in 2021 (33.3%). The most represented countries were the United States, the United Kingdom, and Taiwan, with the National Early Warning Score (NEWS) being the most frequently used tool (33.3%). All studies demonstrated that early warning tools, such as NEWS and MEWS, were effective in preventing adverse events, including cardiorespiratory arrest and death. Thus, it is concluded that the use of clinical deterioration detection tools is applicable in various hospital settings and can support the identification of cardiorespiratory arrest and other adverse events, contributing to improved patient safety and the quality of healthcare.